Effect of HPMC on solubility and dissolution of carbamazepine form III in simulated gastrointestinal fluids - Bhise, S B; Rajkumar, M (Asian Journal of Pharmaceutics (AJP), 2014)
The effect of HPMC on solubility and dissolution of carbamazepine form III (CBZ) was investigated in 50% w/w of CBZ form III in HPMC solid dispersion and physical mixture. Powdered samples of CBZ form III, physical mixture, and solid dispersion were characterized for thermal behavior (DSC), crystallinity (PXRD), and compatibility (FT-IR). Solubility and dissolution studies were carried out in different simulated gastrointestinal fluids and de-ionized water. Solubility studies in simulated gastric fluid (SGF) revealed that acidic pH favors formation of CBZ dihydrate.Triton X 100 in blank fast-state simulated gastric fluid (FaSSGF) prevents the formation of CBZ dihydrate in acidic pH. A maximum solubility of 268.77 Î¼g/mL was achieved with fed-state simulated intestinal fluid (FeSSIF). Correlation between solubility and pH could not be established. Both solubility and dissolution studies revealed that HPMC had a profound effect of enhancement of solubility and dissolution of CBZ form III in both physical mixtures and solid dispersions. HPMC prevents the formation of CBZ dihydrate and thereby improves the solubility and dissolution. This was further correlated with results obtained from DSC and XRD. There was no drastic difference in solubility and dissolution of CBZ form III with different media. It was observed that there was no existing relationship between solubility and dissolution of CBZ form III in different media.